UPAYA MENINGKATKAN MINAT MEMBACA AL QUR’AN ANAK USIA DINI DENGAN MEDIA BAHAN BEKAS DI PAUD INAYAH HAKIKI - Nurhafni, Nurhafni (Jurnal Al-Fatih, 2024)
This study aims to improve young children's interest in reading the Qur'an through the use of recycled materials (paper) as a learning medium at PAUD Inayah Hakiki, Sungai Raja Village, NA IX–X District, Labuhanbatu Utara Regency. This research employed a Classroom Action Research (CAR) design, conducted in two cycles. Each cycle consisted of the stages of planning, action implementation, observation, and reflection. The subjects of the study were early childhood students, while data were collected through observation, interviews, and documentation, and analyzed descriptively and qualitatively. The results showed an increase in children's interest and ability to read the Qur'an after the implementation of recycled material media. In Cycle I, the children's ability levels were 35% fluent, 15% moderate, and 50% low, whereas in Cycle II they improved to 40% fluent, 15% moderate, and 45% low. This improvement indicates that learning using recycled materials made children more interested, active, and enthusiastic in recognizing and pronouncing hijaiyah letters correctly according to their articulation points. Therefore, the use of recycled materials proved effective in enhancing young children’s interest in reading the Qur'an, offering a creative and engaging alternative learning strategy in early childhood education settings.